USING KWL (KNOW, WANT TO KNOW, LEARNED) STRATEGY IN TEACHING READING ANALYTICAL EXPOSITION TEXTS TO THE ELEVENTH GRADE OF MA MIFTAHUL ULUM GRESIK - Frederich Jovan Leonardo; Faishol Hadi (Journal of English Language Teaching and Islamic Integration, 2026)
This study aimed to describe the implementation of the KWL (Know, Want to Know, Learned) strategy in teaching reading comprehension of analytical exposition texts  and  to  investigate  students’  responses  toward  its  use.  The  study  employed  a descriptive qualitative method involving the eleventh-grade students of MA Miftahul Ulum Gresik as the research subjects. Data were collected through questionnaires and classroom observation. The findings revealed that the KWL strategy was implemented effectively through three stages: activating students’ prior knowledge, guiding students to formulate questions, and encouraging reflection after reading. The use of relevant analytical  exposition  text  topics  helped  increase  students’  engagement  and comprehension.  The  questionnaire  results  indicated  that  most  students  responded positively  to  the  KWL  strategy,  showing  improved  understanding,  motivation,  and participation in reading activities. Based on the findings, it can be concluded that the KWL  strategy  is  an  effective  and  student-centered  approach  for  teaching  reading comprehension of analytical exposition texts in EFL classrooms.